Afronauts: Race in Space. Issue 2 (3rd March 2020) - Ian Bourland, W
Abstract: This article historicises and applies a critical framework to key themes in Afrofuturist cultural production. Building on recent popularisations of tropes of black futurity and Afrocentrism, it analyses the figure of the 'afronaut' as it has appeared in a range of contemporary art practices in Europe, the United States, and Africa. The author roots the afronaut in a visual cultural lineage of science fiction and argues that, in recent history, artists deploy this figure to an array of socio-political and epistemological ends.